2022
DOI: 10.3389/fneur.2022.773265
|View full text |Cite
|
Sign up to set email alerts
|

The Emesis Trial: Depressive Glioma Patients Are More Affected by Chemotherapy-Induced Nausea and Vomiting

Abstract: PurposeGlioma patients face a limited life expectancy and at the same time, they suffer from afflicting symptoms and undesired effects of tumor treatment. Apart from bone marrow suppression, standard chemotherapy with temozolomide causes nausea, emesis and loss of appetite. In this pilot study, we investigated how chemotherapy-induced nausea and vomiting (CINV) affects the patients' levels of depression and their quality of life.MethodsIn this prospective observational multicentre study (n = 87), nausea, emesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, even with maximal therapy, the 5-year survival rate is < 5%; therefore, the present treatment goal is to maximize QoL [ 70 ]. Many studies have highlighted the necessity to consider QoL issues in the treatment of gliomas [ 74 , 75 ]. In a prospective multicenter study ( n = 87), patients with gliomas treated with chemotherapy had higher levels of depression, higher chemotherapy-induced nausea and vomiting, and lower QoL at all time points.…”
Section: Depression and Qol In Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…However, even with maximal therapy, the 5-year survival rate is < 5%; therefore, the present treatment goal is to maximize QoL [ 70 ]. Many studies have highlighted the necessity to consider QoL issues in the treatment of gliomas [ 74 , 75 ]. In a prospective multicenter study ( n = 87), patients with gliomas treated with chemotherapy had higher levels of depression, higher chemotherapy-induced nausea and vomiting, and lower QoL at all time points.…”
Section: Depression and Qol In Gliomamentioning
confidence: 99%
“…In a prospective multicenter study ( n = 87), patients with gliomas treated with chemotherapy had higher levels of depression, higher chemotherapy-induced nausea and vomiting, and lower QoL at all time points. Therefore, the researchers suggested that depressive symptoms in patients with cancers should be recognized and treated to avoid the more serious side effects of cancer treatment [ 75 ]. QoL encompasses symptom control; functional status, such as the ability to carry out activities of daily living; emotional health, such as the control of depression and anxiety; and social health, including the possibility of maintaining personal, family, and social roles and gaining access to social support [ 76 ].…”
Section: Depression and Qol In Gliomamentioning
confidence: 99%
“…Moreover, treatments of glioma (such as surgery, chemotherapy, etc.) may impose negative influences on their mental health, too ( 15 , 16 ). Therefore, the mental health of glioma patients is a major issue currently.…”
Section: Introductionmentioning
confidence: 99%